PENINGKATAN KOMPETENSI ORGANIS GEREJA DALAM MENGIRINGI NYANYIAN JEMAAT MELALUI PELATIHAN MUSIK LITURGI DI HKBP DISTRIK X MEDAN-ACEH - Azwar Anas Pasaribu (Penerbit Widina, Widina Media Utama, 2025)
Congregational singing plays a vital role in the liturgical life of the church as a means of fostering faith and theological reflection, particularly within the HKBP tradition through the Ende Book; however, there are still organists who do not fully understand accompaniment techniques, thereby failing to fully support the spiritual experience of worship. This study aims to enhance the understanding and skills of church organists in accompanying congregational singing appropriately and in a liturgically sound manner. The method used was participatory training through the presentation of materials, musical demonstrations, hands-on practice, and discussions on accompaniment techniques, including the interpretation of lyrics, rhythm and meter, tempo control, dynamics, phrasing, staccato, and the combination of instrumental registers. The activity was conducted during a training session for HKBP District X Medan-Aceh organists, involving church music ministers. The results showed an increase in participants’ understanding of the relationship between theological meaning and musical technique, as well as improved skills in tempo control, dynamics, and phrasing to support congregational participation. Thus, this training contributed positively to improving the quality of church music ministry, making congregational singing accompaniment more orderly, expressive, and supportive of the worship experience. ABSTRAKNyanyian jemaat memiliki peranan penting dalam kehidupan liturgi gereja sebagai sarana pembinaan iman dan refleksi teologis, khususnya dalam tradisi HKBP melalui Buku Ende, namun masih terdapat organis yang belum memahami teknik pengiringan secara optimal sehingga kurang mendukung penghayatan ibadah. Penelitian ini bertujuan untuk meningkatkan pemahaman dan keterampilan organis gereja dalam mengiringi nyanyian jemaat secara tepat dan liturgis. Metode yang digunakan adalah pelatihan partisipatif melalui penyampaian materi, demonstrasi musik, praktik langsung, dan diskusi mengenai teknik pengiringan, meliputi penghayatan syair, irama dan birama, pengaturan tempo, dinamika, frasering, staccato, serta kombinasi register instrumen. Kegiatan dilaksanakan pada pembekalan organis HKBP Distrik X Medan-Aceh dengan melibatkan pelayan musik gereja. Hasil menunjukkan peningkatan pemahaman peserta terhadap hubungan makna teologis dan teknik musikal, serta peningkatan keterampilan dalam pengaturan tempo, dinamika, dan frasering untuk mendukung partisipasi jemaat. Dengan demikian, pelatihan ini berkontribusi positif dalam meningkatkan kualitas pelayanan musik gerejawi sehingga pengiringan nyanyian jemaat menjadi lebih tertib, ekspresif, dan mendukung penghayatan ibadah.